Plants vs. zombies (2015), volume 17 ebook Multi-ball-istic. - Tobin, Paul (Plants vs. Zombies (2015), 2020)
Will Flora the Sunflower and Neighborville's plant platoon hit a triple-bonus combo or will their efforts ride the outlanes to certain loss? Enjoy this hilariously pinball-primed Plants vs. Zombies tale crafted by series veteran Paul Tobin!Plunge into another battle between plants and zombies as Dr. Zomboss turns the entirety of Neighborville into a giant, fully-functional pinball machine! With bumpers, flippers, and pegs meticulously scattered across town by the zombie pinball wizard himself, Nate, Patrice, and their plant posse must find a way to revert Neighborville to its normal state and halt this uniquely horrifying zombie invasion. With every ball and bumper set against them, will they hit a run of zombie knock-out skill shots--or will the battle go full tilt zombies?! Eisner Award-winning writer Paul Tobin (Bandette, Genius Factor) collaborates with artist Christianne Gillenardo-Goudreau (Plants vs. Zombies: Better Homes and Guardens) for a brand-new Plants vs. Zombies journey! Author: Paul Tobin. Illustrator: Christianne Gillenardo-Goudreau, Heather Breckel, Steve Dutro.